Durability of response to immune checkpoint inhibitors in metastatic Merkel cell carcinoma after treatment cessation. (April 2023) - Weppler, Alison M.; Da Meda, Laetitia; Pires da Silva, Ines; Xu, Wen; Grignani, Giovanni; Menzies, Alexander M.; Carlino, Matteo S.; Long, Georgina V.; Lo, Serigne N.; Nordman, Ina; Steer, Christopher B.; Lyle, Megan; et al.
Abstract: Background: Metastatic Merkel cell carcinoma (mMCC) is highly responsive to immune checkpoint inhibitors (ICIs); however, durability of response after treatment cessation and response to retreatment in the setting of progression is unknown. Methods: Patients (pts) having mMCC from 10 centres who discontinued ICI treatment for a reason other than progression were studied. Results: Forty patients were included. Median time on treatment was 13.5 months (range 1–35). Thirty-one patients (77.5%) stopped treatment electively while 9 patients (22.5%) stopped due to treatment-related toxicity. After median of 12.3 months from discontinuation, 14 pts (35%) have progressed (PD). Disease progression rate following ICI discontinuation was 26% (8 of 31) in patients who discontinued in complete response (CR), 57% (4 of 7) in patients in partial response and 100% (2 of 2) in those with stable disease. Median progression-free survival (PFS) after treatment cessation was 21 months (95% confidence interval [CI], 18- not reached [NR]), with a third of patients progressing during their first year off treatment. PFS was longer for patients who discontinued ICI electively (median PFS 29 months; 95% CI, 21-NR) compared to those who stopped due to toxicity (median PFS 11 months; 95% CI, 10-NR). ICI was restarted in 8 of 14 pts (57%) with PD, with response rate of 75% (4 CR, 2 partial response, 1 stable disease, 1 PD). Conclusion: ICI responses in mMCC do not appear durable off treatment, including in patients who achieve a CR, though response to retreatment is promising. Extended duration of treatment needs to be investigated to optimise long-term outcomes. Highlights: Analysis of durability of response after ICI discontinuation in mMCC patients ( n = 40). Patients stopped ICI for any reason other than progression. mPFS from discontinuation for entire cohort was 21 months (95% CI 18 – NR). Overall considerable rate of progression, but lower if in a CR. Response rate of 75% (6 of 8) to retreatment with same ICI upon progression.